Enhanced performance of nano-palm oil ash-based green mortar against sulphate environment. (November 2020) - Samadi, Mostafa; Huseien, Ghasan Fahim; Lim, Nor Hasanah Abdul Shukor; Mohammadhosseini, Hossein; Alyousef, Rayed; Mirza, Jahangir; Rahman, Ahmad Baharuddin Abd
Abstract: This study aimed to investigate whether the qualities and performance of the nano-palm oil fuel ash (NPOFA) mortar can be improved by substituting it for the ordinary Portland cement (OPC). The method of ball milling was employed to decrease the micron size of palm oil fuel ash to nanosize. The amount of the nanosized palm oil waste used as OPC substitute was nearly 80%, while the fine aggregates and blended ashes had a mass ratio of 3 to 1. Cubic specimens were prepared and cured in water for 28 days followed by exposure to 5% sodium sulphate solution for nearly one and half year. Visual observations, mass transformation and reduction in compressive strength formed the basis for the performance assessment of proposed green mortars. Several micro-structural methods were employed to inspect the degeneration including X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM), etc. Experimental findings revealed that unlike OPC, NPOFA-based mortars were less susceptible to sulphate solution since it contained a lower proportion of OPC. Furthermore, NPOFA-based green mortars were less porous and more resistant to cracks because of the greater crystallinity induced by the reactive silica within NPOFA. It was concluded that, via proper treatment, the palm oil waste can be used for the large scale production of strong, durable and sustainable mortars which could be beneficial to the construction sectors. Highlights: Green mortars with improved durability and mechanical traits were made from nano-POFA. Mortars with high nano-POFA content showed enhanced performance against acid and sulphate attacks. The capacity to create sustainable mortars via nano-POFA inclusion was demonstrated.